Non Adherence to Fluid Restriction among Patients who Undergoing Hemodialysis and Influencing Factors: Study at RSI Sakinah Mojokerto - Muhammad Zulfikar Asumta; Herin Mawarti; Siti Urifah; Yuni Ernawati; Mukhoirotin (Universitas STRADA Indonesia, 2024)
Background: Nonadherence to Fluid Restriction is main problem among chronic renal failure patients who undergoing hemodialysis, it causingan undesirable effect on health and risk of death. Several factors such as sociodemographic, knowledge, susceptibility of illness, perceived treat, perceived controlare some factors influencing Nonadherence behavior. Purpose: The aim of this study was to analyze the factors influencing Non-adherence to Fluid Restriction who undergoing hemodialysis at RSI Sakinah Mojokerto. Methods: A descriptive analytic with crossectional techniques was conducted among 73 patients undergoing hemodialysis at RSI Sakinah Mojokerto by using purposive sampling technique. Data were collected through checklist and questionnaires. Descriptive statistic was used for data analysis and logistic regression test was used analysis the predictor of factors relating with Non-adherence to Fluid Restriction who undergoing hemodialysis. Results: The results of this study showed 37% patients were Non-adherence to Fluid Restriction and 63% patients were adherence. There were three risk factors for non-adherencee, namely (Health Belief Model) HBM, history of disease and length of time undergoing hemodialysis. HBM 0.132 times higher (95% CI: 0.132, 0.035), history of disease 0.072 times higher (95% CI: 0.072, 0.012), and length of time undergoing hemodialysis 0.071 times higher (95% CI: 0.071, 0.016). Conclusion: HBM, history of disease and length of time undergoing hemodialysis were risk factors for Non-adherence to Fluid Restriction. The nurse should consider the patient's adherence with fluid restrictions in providing nursing care.